PENGARUH TAKARAN PUPUK NITROGEN DAN SILIKA TERHADAP PERTUMBUHAN AWAL TEBU (Saccharum officinarum L.) PADA INCEPTISOL - , RISVA APRIAN HARJANTI, Prof. Dr. Ir. Tohari, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted from April until August 2013 at field trial Tridarma, Faculty of Agriculture, Gadjah Mada University, Yogyakarta. The aim of the research was to study the effect of silica and nitrogen on sugarcane growth. The research was done by Completely Randomized Design with three replication. The first factor was urea dosage as nitrogen source consist of 0 kg/ha, 150 kg/ha, 300 kg/ha, 450 kg/ha. The second factor was Si-PlusHS dosage as silica source, consist of 0 kg/ha, 250 kg/ha, and 500 kg/ha. Variety of sugarcane which used is Bululawang which planted at inceptisol using polybag. The observation variables includes plant height, leaf number, leaf area, leaf greenness, stem diameter, internode number, seedlings, root volume, root length, shoot fresh weight, root fresh weight, total fresh weight, shoot dry weight, root dry weight and total dry weight. The result showed that there was an interaction between nitrogen and silicate on plant height, stem diameter, internode number, seedlings, total fresh weight, shoot fresh weight, root fresh weight, root dry weight and total dry weight. Dosage 150 kg/ha urea with 250 kg/ha Si-PlusHS performed well in the observation variables includes plant height, leaf number, leaf area, stem diameter, internode number, root length, root volume, shoot fresh weight, root fresh weight, total fresh weight, shoot dry weight, root dry weight and total dry weight.